PSYCHIATRIC WARD IN GENERAL HOSPITAL: PROFESSIONALS VIEW WHO WORKS IN GENERAL HOSPITAL - Jacó Fernando Schneider; Jucéli Zimmermann Mion (Universidade Federal de Goias, 2003)
The proposal of this study was the one of looking for the professionals of health that act in generalhospital, the perception and the acceptance of the same ones on the possible implantation of psychiatric beds inthe institution close to in that act. The research was accomplished at five private general hospitals of the city ofCascavel, State of Paraná, that you/they render attendance not only to patient of the municipal district but of everywest area of the state of Paraná.